Speech Acts Used In The Film “ The Curious Case Of Benjamin Button” - Hendri Hendri (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
From the analysis, I found that the kinds of speech acts in dialogues of the film was dominated by directive speech acts, 340 times or 68%. The second speech act performed was commisive, 64 times or 13%. The third type of speech acts was expressive, 53 times or 11%. The last type of speech acts was representative, 42 times or 8%.. There was no declaration found in the dialogues of the film. Directive is attempt by the speaker to get the addresse to do something, it influnced by the status between the speaker and the hearer. Commisive commits the speaker to some future course of act. Representative commits the speaker to the truth of the expressed proposition, it also deals with the use of language to tell people how things are. Expressive is used to express our feeling and attitudes. In declarative, the person performing the act must have authority to do it, and must do it in appropriate circumstance and with appropriate actions. Students can learn from the film how people speak and how they perform an act by saying something and learn by using role-play. For learners, it is also an interesting thing watching film by observing the way people speak. At least it will give them inputs in terms of custom, behavior and also values hidden in the film.